13th AIAA/CEAS Aeroacoustics Conference (28th AIAA Aeroacoustics Conference) 2007
DOI: 10.2514/6.2007-3653
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nonlinear and Near-Field Effects in Jet Noise Using Nonlinearity Indicators

Abstract: In the collection and analysis of high-amplitude jet noise data for nonlinear acoustic propagation, both model-scale and full-scale measurements have limitations. Model-scale measurements performed in anechoic facilities are usually limited by transducer and data acquisition system bandwidths and maximum propagation distance. The accuracy of fullscale measurements performed outdoors is reduced by ground reflections and atmospheric effects. This paper describes the use of two nonlinearity indicators as compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…For each boom location, 2 20 samples of time waveform data were acquired with a 24-bit Motu 896 recorder at 192 ksamples/s, but the maximum analysis frequency was limited to 75 kHz because of the 6.35 mm microphones' frequency response. 12 The boom's axis was located 4 D j downstream of the nozzle exit plane. This location is within the visible Mach-wave radiation region of the jet [see the Schlieren visualization in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For each boom location, 2 20 samples of time waveform data were acquired with a 24-bit Motu 896 recorder at 192 ksamples/s, but the maximum analysis frequency was limited to 75 kHz because of the 6.35 mm microphones' frequency response. 12 The boom's axis was located 4 D j downstream of the nozzle exit plane. This location is within the visible Mach-wave radiation region of the jet [see the Schlieren visualization in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In earlier research performed by Blackstock (personal communication) it was shown that nonlinearities should be considered in studying jet noise propagation. A recent investigation on identifying nonlinear propagation was performed by Gee et al (2007), 34 that was mainly based on bispectral analysis. The investigation was limited to single sensor analysis and was therefore spatially isolated.…”
Section: Iiib Application Of Pod Based Spectral Hose To An Axisymmementioning
confidence: 99%
“…Applications can be found in the literature and include the work of Mclnerny & Ölcmen (2005), Petitjean et al (2006), Gee et al (2007a) and Kuo et al (2010). Originally derived by Morfey & Howell (1981), this indicator starts with the general from of the Burgers equation for spherically outgoing waves.…”
Section: Definitions With Examplesmentioning
confidence: 99%
“…These bispectral methods identify nonlinearities by computing the quadratic bicoherence, which is essentially the second-order variant of the well-known linear coherence. By applying these techniques one can essentially identify the frequencies at which two signals are linearly and nonlinearly related (Gee et al , 2007a. Since the bispectral technique is an identification technique and does not provide the direct capability of estimation and prediction, another technique, developed in the field of system identification, was introduced which started with the work of Tick (1961).…”
Section: Nonlinear Acousticsmentioning
confidence: 99%